Contributions of Hamstring Stiffness to Straight-Leg-Raise and Sit-and-Reach Test Scores - Miyamoto, Naokazu; Hirata, Kosuke; Kimura, Noriko; Miyamoto-Mikami, Eri (International Journal of Sports Medicine, 2018)
The passive straight-leg-raise (PSLR) and the sit-and-reach (SR) tests have been widely used to assess hamstring extensibility. However, it remains unclear to what extent hamstring stiffness (a measure of material properties) contributes to PSLR and SR test scores. Therefore, we aimed to clarify the relationship between hamstring stiffness and PSLR and SR scores using ultrasound shear wave elastography. Ninety-eight healthy subjects completed the study. Each subject completed PSLR testing, and classic and modified SR testing of the right leg. Muscle shear modulus of the biceps femoris, semitendinosus, and semimembranosus was quantified as an index of muscle stiffness. The relationships between shear modulus of each muscle and PSLR or SR scores were calculated using Pearson’s product-moment correlation coefficients. Shear modulus of the semitendinosus and semimembranosus showed negative correlations with the two PSLR and two SR scores (absolute r value≤0.484). Shear modulus of the biceps femoris was significantly correlated with the PSLR score determined by the examiner and the modified SR score (absolute r value≤0.308). The present findings suggest that PSLR and SR test scores are strongly influenced by factors other than hamstring stiffness and therefore might not accurately evaluate hamstring stiffness.
Keywords: range of motion; ultrasound shear wave elastography; biceps femoris; semitendinosus; semimembranosus